Design and development of sling based squash ball launcher / Muhammad Izzuddin Mohd Sobri - Mohd Sobri, Muhammad Izzuddin (2022)
Final year project consists of the design and development of sling-based squash ball launcher which basically design a projectile launcher which launch the squash ball. The main reasons why the project should be done is to solve the problems that occurred in the school where the student and teacher are having problem with their learning and studies. In this product, it should implement the concept of projectile motion which also involving the components of projectile motion. The final product should be able to achieve the objectives which are able to shoot the cotton ball based on own design and most importantly to observe the components of projectile motion such as initial velocity and angle of launch when the results are obtained through the test run process. Test run process is one of the processes that will be involved in the making of this project. Throughout the process, the product will be tested until it complies all the objectives and meet the expectation of the project. Several process of research will be done to make this project a success which involving what materials should be used, what kind of data collection method that will be used and what kind of data variables should be used. To achieve the final product, it also must undergo the fabrication process which also involving the process of fabricating to make sure the final product is well functioned.